Strategi Pengembangan Teknologi PAI Berbasis Spiritualitas - Febri, Mohammad febri irawan saputra; Acetylena, Sita (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The implementation of technology in Islamic Religious Education (PAI) is often superficial and neglects spiritual development. This study aims to formulate a strategy for developing PAI technology oriented towards soul purification (tazkiyatun nafs) by adopting the TPACK framework centered on spirituality. Using the qualitative Design-Based Research (DBR) method, this study iteratively designed and evaluated a technology prototype. The results indicate that the "Digital Heart" prototype successfully enhanced the transformative learning experience and formulated three fundamental design principles: facilitating personal reflection, contextualizing content, and synergizing digital-communal experiences.